TRADUZIR PALAVRAS, APROXIMAR CULTURAS: O ENSINO DA INTERPRETAÇÃO DE ACOMPANHAMENTO NO ISCAP - Couto, Alberto (2019)
In a society where the migration paths design a new socialization context and where globalization leads to an unfathomable rise of the intercultural meetings, it’s important to refocus the importance of community interpreting training. The release of the Master’s in Specialized Translation and Interpreting in 2007/2008 at the Institute of Accounting and Administration of Oporto, based on the homonymous five-year degree, presented a curricula design in Interpreting with a far more pragmatic understanding. Thus, to the traditional division between Simultaneous and Consecutive Interpreting succeeded the introduction of the disciplines of Conference Interpreting, Remote and Teleconference Interpreting and Liaison Interpreting. The purpose of this essay is to present and discuss different pedagogical approaches tried out during the implementation of the discipline of Liaison Interpreting, based on a scientific/pedagogic reflection, filtered by the most recent tendencies of investigation in this area. The designation “Interpretação de Acompanhamento” (Liaison Interpreting) was adopted by us to describe a communicative situation which takes place in heterogeneous and diverse contexts, in detriment of other designations of a more restrict sense like Escort / Ad Hoc Interpreting – which tend to lead us to a business or cultural or even touristic area of influence – and Community Interpreting - reporting to the linguistic mediation of someone that do not speak the language of the majority, usually in a legal, social or health scope. Therefore, we will be focusing our attention in the following questions: Which pedagogical strategies are best adapted to the teaching of this discipline? How to reproduce the heterogeneity of the communicative contexts that Liaison Interpreting involves inside a class room? In comparison with the intercultural mediation skills, what importance should the linguistic performance assume? How to teach concepts and theories to the Liaison Interpreting area of expertise?